Study of Crystal Growth Phenomenon During the Synthesis of Wollastonite Utilizing Amorphous Silica - Nizam, M. Sharif; Hussain, K. (Biological Sciences - PJSIR, 2007)
Wollastonite (CaSiO), a mineral of wide i ndustrial application , was synthesized under sol id state condi tions. Starting material s for th e synthesis were CaO resul ti ng from the in-situ thermal decomposi tion of limeston e and amorphous silica obtai ned by controlled pyro-processing of rice husk. A mineral izer havi ng glass like composition was prepared and i ntermi xed with th e raw materi al s pul verized to 75 µ particle size. The compact powder batches were si ntered at 900- 1 300 QC for I h i n order to grow wol l astonite crystals from matrix of the reacti ng oxides. The reaction was monitored simu ltaneously by specific ch emical analysis and XRD techniques . Sol id state reactions, invol vi ng orientation and geometrical resh u ffi ing of the interacti ng and newly produced phases, require special considerations for th e product crystal growth . Three possible reaction models, under which the wollaston ite crystal s may grow in reacti ng solids were considered and the generated data treated according to the laid down criteria . The nuclei growth model was conseq uently found to be promisin g as the route adopted by the present solid state reaction yielding wollastonite.